The Relation Of Placenta Previa With History Of Previous Cesarean Section And Miscarriages - Tarza Taha Ahmed; Sallama Kamel Nasir (Advanced Medical Journal)
Background and objectives: The factors that increase the risk of placenta previa in subsequent pregnancies include past miscarriages and the scar from a previous cesarean operation. This study aimed to determine whether a history of cesarean section or miscarriage was related to placenta previa at Sulaimani Maternity Teaching Hospital.